Interacting threats and challenges in protecting danau sentarum - Heri, V.; Yuliani, L.; Indriatmoko, Y. (2010)
Danau Sentarum was declared a conservation area by the government in 1981, was established as a Ramsar wetland conservation area in 1984 and became a 132,000 ha national park with a 65,000 ha buffer zone in 1999. But being named a wetland of international importance and having national park status do not mean that Danau Sentarum receives more attention and better management. Forest cover within and around the park is declining rapidly. The fish stocks and water quality of the wetlands and river network are threatened. Logging has left large tracts of open land, destroyed wildlife habitat and reduced wildlife populations. The Pulau Majang forest, formerly an orangutan habitat, is now devoid of orangutans. Tree felling and land clearing have also triggered human-animal conflict, apparently because forest food sources have fallen drastically, forcing wild animals to seek food in human settlements. This paper aims to identify the interacting threats and underlying causes of the ecosystem degradation and declining resources. The research serves as a baseline study for a larger research project: Promoting Good Governance of Protected Areas Management, being conducted by CIFOR and Riak Bumi Foundation since early 2005.